2007
DOI: 10.1111/j.1467-9477.2007.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

E Pluribus Unum: Diversity and Community in the Twenty‐first Century The 2006 Johan Skytte Prize Lecture

Abstract: Ethnic diversity is increasing in most advanced countries, driven mostly by sharp increases in immigration. In the long run immigration and diversity are likely to have important cultural, economic, fiscal, and developmental benefits. In the short run, however, immigration and ethnic diversity tend to reduce social solidarity and social capital. New evidence from the US suggests that in ethnically diverse neighbourhoods residents of all races tend to ‘hunker down’. Trust (even of one's own race) is lower, altr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

136
3,197
49
151

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 3,588 publications
(3,533 citation statements)
references
References 118 publications
136
3,197
49
151
Order By: Relevance
“…Both strategies have been used in those, relatively few, studies that do not disregard members of minority groups altogether. Some of these studies report a weaker (Putnam, 2007;Stolle et al, 2008; similarly an earlier analysis of the data used in this paper, see Koopmans and Schaeffer, 2016), others no significant relation between diversity and social cohesion measures among minority members (Bakker & Dekker, 2012;Fieldhouse & Cutts, 2010). But while such analyses acknowledge the possibility of effect heterogeneity between majority and minority respondents, they still disregard another ambiguity of diversity indices.…”
Section: In-group Share and Relational Out-group Entropy Or Why Intesupporting
confidence: 47%
“…Both strategies have been used in those, relatively few, studies that do not disregard members of minority groups altogether. Some of these studies report a weaker (Putnam, 2007;Stolle et al, 2008; similarly an earlier analysis of the data used in this paper, see Koopmans and Schaeffer, 2016), others no significant relation between diversity and social cohesion measures among minority members (Bakker & Dekker, 2012;Fieldhouse & Cutts, 2010). But while such analyses acknowledge the possibility of effect heterogeneity between majority and minority respondents, they still disregard another ambiguity of diversity indices.…”
Section: In-group Share and Relational Out-group Entropy Or Why Intesupporting
confidence: 47%
“…It allows us to visualize social relationships and determine who interacts with whom. This is important because these networks of communication either enhance or impede social capital [29,36,37]. We found that trainees do not typically discuss information around breastfeeding, and if they were to do that, they would not only reach out to medical professionals with assumed evidence-based knowledge (e.g., attending pediatrician or attending gynecologist).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the presence of street trees might be hypothesized to encourage physical activity by providing shade in the summer; however, we found that the association between street trees and physical activity tended to be stronger in the cooler months, calling this hypothesis into question. Likewise, bias due to self-selection may be particularly strong among adults and advantaged social groups who have greater power to match their environment to their preferences; 60 associations that persist within situations of constrained residential choice may increase our confidence in causal inference.…”
Section: Discussionmentioning
confidence: 99%